Аpprobation criteria in determining the quality of school textbooks (Journal of Educational Sciences, 2021)
The article will consider the complex requirements for determining the quality of school textbooks. The main purpose of the study is to make an analysis and conclusions about the requirements for the quality of textbooks used in secondary schools prepared according to the updated standard educational program.The preparation of school textbooks is carried out based on a standard educational program. Compliance with their basic requirements is determined by examinations conducted by competent institutions. The criteria for the examination of school textbooks have been formed.The work on the development of textbook studies in the country is developing mainly in the direction of the preparation of school textbooks. Therefore, the requirements for writing a textbook are also based on secondary educational means. The general task is to systematize the didactic, structural and theoretical requirements for the quality of the textbook and to determine their main features and tasks. But, in addition to the expert centre, special attention is paid to the opinion of public organizations and some activists who consider only individual issues. It can be seen from this that the definition of textbook quality requirements should be determined based on the results of a special and comprehensive study. Therefore, a special scientific project has been organized to consider this issue, and systematic research is being conducted. Therefore, systematic research work is being carried out to address this issue during the implementation of the scientific project.The article formulates the research and its results carried out within the framework of a scientific project: AP09260158 "Scientific and methodological foundations for the development and implementation of a system of criteria for the approbation of educational literature", as well as the importance of theoretical, empirical analysis in the formation of requirements for determining the quality of a textbook.Key words: Quality, requirement, program, empiricism, experiment, didactics.